Orçamento público na história do constitucionalismo brasileiro: a lei 4.320/64 e a permanência do projeto político institucional militar na constituição de 1988. - Oliveira, Lizziane Souza Queiroz Franco de (2019)
The present study seeks to investigate the uses of the public budget in Brazilian historical constitutional, and if its constitutionalisation in 1988 a use other than merely accounting, to satisfy the interests and needs of the community, and it is possible to use in a distinct way of the purely accounting, as a formal law. The way to respond to this question came about through historical research, contextualized with the political and economic aspects. It is assumed that the public budget has been used as a simple instrument of accounting because of its constitutional legal treatment. However, is possible to assert its use as an instrument of economic planning for the realization of the constitutional objectives and satisfaction of the interests and collective needs from its constitutionalisation in a constitutional budget system since 1988, despite of the legal regime inaugurated by Law 4,320 and all administrativeinstitutional framework implemented in the military period. The present research has a descriptive approach, using documentary, doctrinal and jurisprudential sources to present an overview of the historical-constitutional treatment given to the public budget and its use as a normative instrument for the implementation of economic policies of government. For this, an approach was taken on the importance of the public budget in the context of a Democratic State of Law, as an essential tool for the realization of rights, as well as the theory of constitutionalisation under the perspective of irradiating the effects of the norms (or values) of the Constitution other branches of law. A brief incursion into the republican constitutions was also made in order to demonstrate the historical overview of the public budget and its juridical aspect in relation to the political and economic systems in Brazil. In this same sense, economic planning was also analyzed in order to demonstrate that its analysis correlated with the budget is fundamental for understanding the events occurred in Brazil during the twentieth century, especially from the beginning of the first economic and developmental movements in the parents. The analysis of Law 4,320 / 64 was also important in order to demonstrate the uses that were made of the budget before the promulgation of the 1988 Constitution. In addition, the recovery of the memory of the process of this Law contributes to the history of Financial Law and Public Law, as well as for understanding an important aspect of this period: the institutional restructuring of the State required for implementation of the politicaleconomic project of the military government, with banking, monetary, tax and administrative reforms. In view of the uses of the budget in the past, we proceeded to analyze the use of the budget in the Constitution of 1988 and the process of constitutionalisation of the budget from the perspective of the debates that took place in the Constituent Assembly, in order to verify if in the Brazilian case, in 1988, there was a rupture with the previous legal system or if the new order represented a continuation of the political-institutional project until then in force. In view of this, it is possible to affirm that the constitutionalisation of the public budget made possible its use as an instrument of economic planning for the purpose of implementing the constitutional objectives and satisfying the interests and needs of the community; however, the maintenance of the political-institutional structure inaugurated during the military regime has made the use of this use unfeasible, as well as hampering the promotion of the constitutional principles of a Democratic Rule of Law.